PROSES PENYUSUNAN ANALISIS JABATAN ESELON IV DI BKD KOTA SEMARANG (PASCA IMPLEMENTASI UNDANG-UNDANG NOMOR 5 TAHUN 2014 TENTANG ASN) - K.D, Amanda Novitasari; Sulandari, Susi; Yuniningsih, Tri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
One scope bureaucracy reform is the emergence of law on civil state apparatus (UU ASN). Explained that every government institution shall prepare need for the number and type of positions based on job analysis and ABK. This type of research uses descriptive qualitative approach. The focus of the research is to describe the process and inhibiting factors in job analysis drafting process of echelon IV in BKD Semarang city (post- implementation regulation no. 5/2014 about ASN). The subject of research using snow-ball samplling technique, where the informant that is the head of Sub-areas/Sub-section BKD Semarang city, and the head of the Organization Semarang city. Analysis of data reduction and data through triangulation of sources. Starting from the initial stage to socialization of job analysis by Ministry of Internal Affairs, BKN center of Jakarta, part of Organization, and the establishment of team analyzer. Process of collection data positions using the system of observation, questionnaires, interviews, and combined with regulation mayor of BKD Semarang city. Data processed into job information with several times verification and authorized the issuance of the decree of the head of BKD Semarang city. Inhibiting factors in job analysis drafting process of echelon IV in BKD Semarang city, among others: (1) Budgeting, (2) Regulation, (3) Employee, and (4) Team Analyzer. It was concluded that the job analysis drafting process takes a long time and periodically, team analyzer done before drafting of job analysis, the existence of spesific rules in the job information offic, job analysis need several times verification to the incumbent, until the results of a legitimate form of publishing SK from the head of BKD Semarang city. Advice given is the need for early socialization related regulations that will be used, and socialization to employees about job analysis, provision of training for the team analyzer.